Network monitoring and reporting system for Telekom Malaysia streamyx links - Elias, Aswan (2004)
Network Monitoring and Reporting System (NEMORS) is a web-based network monitoring system. This project development is an industrial attachment project for a MSc. in Real-Time Software Engineering course in University of Technology Malaysia, Kuala Lumpur. The project was attached in the Department of Corporate Information Superhighway (COINS) in Telekom Malaysia Berhad (TMB), supervised by the Head of Value Added Network Services (VANS). The system is providing a performance analysis data of the selected Streamyx links used for analysis and planning. The government through the Communication and Multimedia Commission (CMC) are also benefit with the analyzed date used to monitor the quality of the Streamyx services given to customer throughout the country. NEMORS can measure availability, latency, utilization and packet loss in a network. It uses RRDtool to maintain a longterm datastore and to draw pretty graphs, giving up to the minute information on the state of each network connection. It has a smart alarm system which triggered by latency or loss patterns values. It can also notify operator by sending e-mail to alert actions when machines become unavailable, or network response times become too long while all are being recorded in log files. During the project, Extreme Programming was applied as the software methodology throughout the development life cycle. The project adopt the DoD 2167A standard documentation and using the state-of-the-art open source technology used for the operating system, system application and the database system.